EFEK HEPATOPROTEKTOR FRAKSI TIDAK TERSABUNKAN DARI DALMS TERHADAP KONDISI STRES OKSIDATIF PADA TIKUS WISTAR - Yuyun Wahyuni (AGRICA, 2020)
Palm oil fatty acid distillate (POFAD) is a byproduct of the process of refining palm oil, which still contains compounds. As a result of the increasing production of palm oil in Indonesia and POFAD, making POFAD has the potential as a source of tocotrienols, which can act as natural antioxidants and protect the liver against oxidative stress. The purpose of this study was to study the effects of hepatoprotection of the non-atomized fraction of POFAD in vivo and to find out the best dose of non-soapy fraction of POFAD on MDA levels, SOD of rat liver, and histopathological features in oxidative stress conditions due to waste cooking oil intake. The study design used was a Completely Randomized Design (CRD) which was composed of 6 treatment groups consisting of negative (normal), positive (indiscriminate) control groups, non-dose fraction I (100 mg/kg BW) fractions, non-soapy fractions dose II (200 mg/kg body weight), non-atomic dose III (500 mg/kg body weight), the non-dose fraction (1000 mg/kg body weight) and each treatment were repeated four times. Observational data obtained were processed statistically with the ANOVA test and continued with the Smallest Significant Difference Test (BNT) processed with SPSS for Windows 16 series. The results of this study indicate that the non-soapy fraction of palm oil fatty acid distillates has the ability to protect the liver from organ damage to dose III, namely the administration of non-soapy fractions at a dose of 500 mg/kg body weight.